Insights From the Lactobacillus johnsonii Genome Suggest the Production of Metabolites With Antibiofilm Activity Against the Pathobiont Candida albicans - Vazquez-Munoz, Roberto; Thompson, Angela; Russell, Jordan T.; Sobue, Takanori; Zhou, Yanjiao; Dongari-Bagtzoglou, Anna (Frontiers in Microbiology, 2022)
Lactobacillus johnsonii is a probiotic bacterial species with broad antimicrobial properties; however, its antimicrobial activities against the pathobiont Candida albicans are underexplored. The aim of this study was to study the interactions of L. johnsonii with C. albicans and explore mechanisms of bacterial anti-fungal activities based on bacterial genomic characterization coupled with experimental data. We isolated an L. johnsonii strain (MT4) from the oral cavity of mice and characterized its effect on C. albicans growth in the planktonic and biofilm states. We also identified key genetic and phenotypic traits that may be associated with a growth inhibitory activity exhibited against C. albicans. We found that L. johnsonii MT4 displays pH-dependent and pH-independent antagonistic interactions against C. albicans, resulting in inhibition of C. albicans planktonic growth and biofilm formation. This antagonism is influenced by nutrient availability and the production of soluble metabolites with anticandidal activity.